2002
DOI: 10.1074/jbc.c200066200
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Mobility Account for Camptothecin-induced Subnuclear Relocation of Topoisomerase I

Abstract: DNA topoisomerase I is a nucleolar protein, which relocates to the nucleoplasm in response to drugs stabilizing topoisomerase I⅐DNA intermediates (e.g. camptothecin). Here we demonstrate that this phenomenon is solely caused by the drug's impact on the interplay between mobility and localization of topoisomerase I in a living cell nucleus. We show by photobleaching of cells expressing biofluorescent topoisomerase I-chimera that the enzyme moves continuously between nucleoli and nucleoplasm. Complex kinetics of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
57
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 39 publications
(65 citation statements)
references
References 18 publications
8
57
0
Order By: Relevance
“…This pattern is consistent with other data showing that TOP1 is primarily localized to the nucleolus [23], but shuttles between the nucleolus and the nucleoplasm [24,25], and therefore provides further evidence of the specificity of staining. In some Purkinje neurons however, this pattern was reversed, with the amount of TOP1 being lower in the nucleolus than in the nucleoplasm ( Figure 5B, bottom row).…”
Section: Topoisomerase I Is Also Concentrated In the Nucleus Of Purkisupporting
confidence: 92%
See 1 more Smart Citation
“…This pattern is consistent with other data showing that TOP1 is primarily localized to the nucleolus [23], but shuttles between the nucleolus and the nucleoplasm [24,25], and therefore provides further evidence of the specificity of staining. In some Purkinje neurons however, this pattern was reversed, with the amount of TOP1 being lower in the nucleolus than in the nucleoplasm ( Figure 5B, bottom row).…”
Section: Topoisomerase I Is Also Concentrated In the Nucleus Of Purkisupporting
confidence: 92%
“…Also, our localization of the MRN proteins in human Purkinje neurons is completely consistent with the observations of Jacobsen et al [19]. With regard to TOP1, in addition to obtaining identical results using two independently generated monoclonal antibodies, our observation that TOP1 is localized to the nucleolus and nucleoplasm is consistent with other studies on the distribution of this enzyme within the nucleolus [23], and nucleus, including observations of GFP-tagged TOP1 in living human cells [24,25]. It should be noted that in one study [34], cytoplasmic TOP1 staining was observed in the mouse Purkinje neurons.…”
Section: The Mrn-complex and Topoisomerase I Are Also Concentrated Insupporting
confidence: 91%
“…However, we have recently observed that in a living cell topoisomerase I exchanges between nucleoli and the nucleoplasm in a rapid and continuous manner, suggesting that the distribution of the enzyme between these compartments is more likely governed by differences in residence time than by directing signals (2). In keeping with this, we show here that nucleolar accumulation of various truncated versions of topoisomerase I is correlated with their lesser mobility in this compartment and not with the N-terminal portion being intact or present.…”
Section: Discussionmentioning
confidence: 99%
“…In keeping with this, studies of genomic DNA cleavage by topoisomerase I have invariantly come up with sites in the rDNA (3)(4)(5). However, catalytic interactions with rDNA cannot per se account for the accumulation of topoisomerase I in the nucleoli because stabilization of covalent topoisomerase I⅐DNA intermediates by camptothecin immobilizes the enzyme preferentially at nucleoplasmatic sites and only to a much lesser extent in the nucleoli (2). Along this reasoning the question arises of what restricts topoisomerase I in the nucleolus and how is this phenomenon related to rDNA processing.…”
mentioning
confidence: 98%
See 1 more Smart Citation